The Gaia-ESO Survey: evidence of atomic diffusion in M67? - Bertelli Motta, Clio; Pasquali, Anna; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Investigating the chemical homogeneity of stars born from the same molecular cloud at virtually the same time is very important for our understanding